Exploring the structural integrity of a picornavirus capsid - Upfold, Nicole Sarah (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
Picornaviruses are a diverse family of small RNA viruses that cause a broad range of human and veterinary diseases. Despite decades of research into the molecular biology of these pathogens, no antivirals and few vaccines are commercially available for the treatment and prevention of picornavirus infections. The capsids of these non-enveloped viruses are involved in many important aspects of the picornavirus lifecycle, such as cell attachment and entry, uncoating, and protection of the viral RNA. Although the structures of many picornavirus capsids have been solved, a broader understanding of the molecular determinants that are required for structural integrity and stability is imperative for an improved understanding of the basic biology of these viruses, and for designing effective control strategies. Collectively, this thesis aims to elucidate the molecular determinants of structural stability and integrity in the Theiler's murine encephalomyelitis virus capsid (TMEV). To study the TMEV GDVII capsid using biochemical techniques, neutralising polyclonal antibodies were generated against GDVII particles. The antibodies recognised linear epitopes in the C-terminus of the VP1 protein, but not those present in VP2 or VP3. The VP1 C-terminal residues were mapped to a loop above the putative receptor binding pit on the capsid surface, which prompted an investigation into the potential binding site of the TMEV co-receptor, heparan sulphate. Molecular docking revealed that heparan interacts with residues of the receptor binding pocket, as well as residues of the adjoining VP1 C-terminal loop. These findings suggest that the antibodies neutralise virus infection by preventing attachment of the virus to the co-receptor and possibly the unknown primary receptor. Few studies have identified the specific residues and interactions at subunit interfaces that significantly contribute to picornavirus capsid stability, assembly, and function. A novel in-silico screen was developed for the prediction of hotspot residues at protein-protein interfaces of a virus capsid. This screen can be applied to elucidate the residues that contribute significantly to the intraprotomer, interprotomer and interpentamer interfaces of any picornavirus capsid, on condition that the structure of the virus is available. The screen was applied to TMEV GDVII resulting in the identification of hotspots, several of which correspond to residues that are known to be important for aspects of the virus lifecycle, such as those that contribute to pH stability or form part of receptor binding sites. This observation suggests that residues involved in specific capsid functions may also play a role in capsid stability. Many of the residues identified as hotspots in TMEV corresponded to those required for assembly, uncoating, and virus growth in representative picornaviruses from various genera, suggesting that the residues that regulate capsid stability may be somewhat conserved across the family. Hotspots identified at the interpentamer interfaces of TMEV were individually substituted to alanine to further explore their importance to the TMEV lifecycle. All the amino acid substitutions prevented completion of the virus lifecycle as no CPE was observed following transfection of susceptible cells. Immunofluorescence experiments demonstrated that virus protein synthesis and RNA replication were not inhibited by substitution of the hotspot residues, but that infectivity was severely impeded. This confirmed that the residues were required for some aspect of the virus lifecycle, such as capsid assembly, or were critical for maintaining the conformational stability of the TMEV particles. Virus capsids become unstable and are prone to dissociation under certain conditions such as extreme pH and non-physiological temperatures. The thermostability of TMEV was explored by selecting GDVII virions with improved thermal tolerance through serial passage and heat exposure. Thermostable virions that could tolerate temperatures above 57 Â°C had reduced infective titres compared to the wild type TMEV suggesting that the virus adapted to thermal stress at the expense of viral fitness. Sequencing the capsid encoding regions of the mutant virions revealed a pair of amino acid substitutions that were present in all mutants. Additional substitutions that were unique to viruses selected at different temperatures were also identified. Most of the substitutions were located within the intraprotomer interfaces of the virus, unlike previous studies on enteroviruses where mutations were mostly localised to the receptor binding pocket. This thesis provides the first analysis of the structural determinants of TMEV capsid stability. The generation of tools to further explore the capsid structures of TMEV and other picornaviruses provides an opportunity for future studies which may contribute to the development of novel control strategies against this important family of viruses.
Keywords: Picornaviruses; Immunoglobulins; Capsids (Virology); Viruses -- Morphology; RNA viruses